TRANSNATIONAL FATWAS ON JIHAD IN INDONESIA - Ansari Ansari (Universitas Islam Negeri Jakarta, 2014)
Transnational Fatwas on Jihad in Indonesia. Fatwa has an important stake in Islamic legal development. Its presence is able to provide influences on person’s religious attitude and behaviour. Although fatwa is a product of ijtihad, it’s still considered as a rule which should be obeyed especially if it is pronounced by a great scholar or authorised body which has wide influence over the community. This paper will study thoroughly the transnational fatwas on jihad which had influenced people’s religious attitude and behavior of many Indonesian Muslims. Fatwas on jihad motivated Indonesian Muslims to carry out violence towards non Muslims. The disturbance on religion became one of the reasons of violent actions towards them.DOI: 10.15408/ajis.v14i1.1238